Experimenting with Embryos: Can Philosophy Help? - Heyd, David (Bioethics, 1996)
Beyond the well-known ethical issues involved in medical experimentation on human subjects, experimenting with embryos raises unique and particularly hard problems. Beside the psychological obstacles connected with the fear of ‘‘playing God' and the awe with which we hold the process of the creation of human beings, there are three philosophical problems which are the main subject of the article: 1. The logical problem of circularity: the morality of experimenting on embryos is dependent on the status of the embryo, which in turn is partly decided by experimentation. 2. The metaphysical problem: experiments are justified by the benefits they bring to human subjects; but it is doubtful whether an early embryo is a ‘‘subject' and whether coming into being is a ‘‘benefit'. 3. The moral problem: the standard constraint on medical experiments is that they benefit either the individual subject or at least members of a relevantly defined group of patients suffering from the same syndrome. But embryo experimentation is often associated with potential cure to people of a completely different category (like geriatric patients). Finally, the article discusses the limits of the force of philosophical arguments in the formation of actual policies for regulating such practices as experimenting with embryos. The widely-shared fourteen-day limit is shown to be a sound practical compromise despite the difficulties in justifying it philosophically.